Costos de producción de la Compañía Carrtcorp S.A. HDA. La Estancia durante el periodo 2020-2021. - Castillo Vera, Erwin Reynaldo (2022)
This case study is focused on the production costs of the company Carrtcorp S.A. HDA La Estancia during the period 2020-2021. The company is dedicated to agricultural development whose purpose is the general sale of its products such as rice, soybeans and corn. Through the information for the 2020-2021 period, it is evident that the company has an inadequate distribution and allocation of production costs. Through the present investigation in this case, we want to direct the company to choose to manage a production cost system where it takes into account the entire process of the material, raw labor and the indirect costs of manufacturing, since which in its 2020-2021 period obtained low profits due to high production costs. To carry it out, concepts of authors and reports relevant to the case of production costs will be taken into account and with the help of descriptive and inductive techniques, it will be possible to choose the implementation of activities related to a contingency plan for the company. Among the conclusions, it was determined that a system of production costs in the company would contribute to controlling costs and consequently obtaining an accurate profitability.